2021
DOI: 10.3390/nano11102633
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Flexible Organic Solar Cell Based on Indium-Zinc-Tin Oxide Transparent Electrode for Power Source of Wearable Devices

Abstract: We have developed a novel structure of ultra-flexible organic photovoltaics (UFOPVs) for application as a power source for wearable devices with excellent biocompatibility and flexibility. Parylene was applied as an ultra-flexible substrate through chemical vapor deposition. Indium-zinc-tin oxide (IZTO) thin film was used as a transparent electrode. The sputtering target composed of 70 at.% In2O3-15 at.% ZnO-15 at.% SnO2 was used. It was fabricated at room temperature, using pulsed DC magnetron sputtering, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Organic solar cells (OSCs) are a prospective class of devices owing to their solution fabrication techniques, high stability, and ability to be flexible, semitransparent, or even colorful, which is important for building-integrated and wearable photovoltaics [ 1 , 2 , 3 , 4 ]. Although the harvesting efficiency of OSCs is constantly increasing, there are still many issues that have to be addressed before commercialization [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) are a prospective class of devices owing to their solution fabrication techniques, high stability, and ability to be flexible, semitransparent, or even colorful, which is important for building-integrated and wearable photovoltaics [ 1 , 2 , 3 , 4 ]. Although the harvesting efficiency of OSCs is constantly increasing, there are still many issues that have to be addressed before commercialization [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Later various alternative TCO materials, such as indium zinc oxide (IZO), zinc indium tin oxide (ZITO), indium tin zinc oxide (ITZO), and indium zinc tin oxide (IZTO) have been tried to overcome the issues faced while using ITO as flexible electrodes. [16][17][18][19][20] Among those TCO materials, IZTO films have exhibited a great potential for use as the transparent anode material in various flexible transparent electronic devices owing to its high transparency, lower sheet resistance, high work function (6.1 eV), and lower processing temperature value. 20 Recently, Heo et al reported a utilization of IZTO film as a transparent electrode of a flexible organic solar cell that exhibited a maximum of 93.3% of its initial power conversion efficiency (PCE) value after bending it a 1000 times (i.e., compression and relaxation tests).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Among those TCO materials, IZTO films have exhibited a great potential for use as the transparent anode material in various flexible transparent electronic devices owing to its high transparency, lower sheet resistance, high work function (6.1 eV), and lower processing temperature value. 20 Recently, Heo et al reported a utilization of IZTO film as a transparent electrode of a flexible organic solar cell that exhibited a maximum of 93.3% of its initial power conversion efficiency (PCE) value after bending it a 1000 times (i.e., compression and relaxation tests). 20 Further, the same group has developed ultra-flexible OPVs with lowtemperature deposited IZTO on a cyclic polymer substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Organic photovoltaics (OPV) has been developing in recent years due to its cost, solution processibility, semi-transparency, mechanical flexibility, light weight, and has become increasingly interesting for technology [ 1 , 2 , 3 ]. The possibility of application in wearable systems, connection to IOT (Internet of Things) and powering personal devices [ 4 , 5 , 6 ] as well as the hope for the use of organic cells in space [ 7 ], causes substantial popularity of the organic photovoltaic.…”
Section: Introductionmentioning
confidence: 99%